Health promotion for women in sociallyvulnerableterritory: community Saroba (Research, Society and Development, 2020)
Objective: To describe the actions of education and health care carried out for women in a situation of socioeconomic vulnerability in Palmas - TO. Methods: This is an experience report of educational actions, health promotion and preventive strategies that addressed the themes of abuse of alcohol and other drugs, sexual and reproductive health, hygiene and also intersectoral actions to solve complex problems for women residing in the Saroba Community. Results: The education actions were based, basically, on four subjects, being addressed in an intersectoral and integral way in the 15 meetings held: the abusive use of alcohol and other drugs, sexual and reproductive health, hygiene of the place, and the opportunity to welcome. The biggest problem found was in relation to the pattern of behavior regarding the more intense consumption of alcohol and other drugs by women, which leads to greater exposure to risks, such as unemployment and, consequently, involvement with illegal activities and prostitution, in addition to the strong relationship with violence and living conditions on the street. Conclusion: Despite the difficulties faced by the group to carry out educational actions, the creation of a bond with the Care Network and the reduction of risky behaviors, it was possible to show that it is possible to integrate local women with health professionals, since that there is total openness and confidence to discuss the themes and effective participation of those involved in the choices.